Leadership Character Building in Students with the Implementation of the Full Day School System at SMPIT Qurota A'yun Ponorogo - Defi Firmansah; Reza Aditya Ramadhani; Dila Rukmi Octaviana (Educan : Jurnal Pendidikan Islam, 2023)
AbstractOne of the efforts of educational institutions in implementing full day school is an alternative way to produce a generation of quality and trustworthy leaders. This study aims to analyze the formation of student leadership characters based on full day schools (Full Day School). The research method uses descriptive qualitative research using observation, interviews and documentation. In collecting data taken from three subjects consisting of principals, teachers, and students. Steps of data analysis through data presentation, data reduction and drawing conclusions. The results of the research show that the process of forming student leadership character based on full day school includes several activities in the system, such as: First, daily school cultural activities include activities that support discipline such as morning apples, morning habits. second, scouting extracurricular activities are carried out after every Friday ba'da, then opening apple activities, UN, Pioneering. Third, student council activities consist of being given a mandate from the P2KS committee and training in Basic Leadership Training.